Review of global agricultural emission databases - Pablo, Elverdin; Said, Andrés D. (International Food Policy Research Institute, 2024)
Since the Industrial Revolution, the concentration of greenhouse gases (GHG) has consistently risen, leading to a 1.15°C increase in global mean temperatures by 2022. The Intergovernmental Panel on Climate Change (IPCC) confirms human activities as the primary cause of global warming, with emissions continuing to rise. Climate change has resulted in adverse impacts on various fronts, disproportionately affecting vulnerable communities. International efforts, including the United Nations Frame-work Convention on Climate Change (UNFCCC) and its Kyoto Protocol, aimed at stabilizing green-house gas concentrations. These efforts were followed by the Paris Agreement in 2015, focusing on limiting global temperature increases and relying on Nationally Determined Contributions (NDC) from countries.